The inheritance : a novel - Goodman, Joanna, 1969- (Harper, 2024)
"From the bestselling author of The Home for Unwanted Girls and The Forgotten Daughter comes a compulsively readable mother-daughter story in which two women who share a difficult past must come to together to claim the future they deserve. Arden Moore enjoyed an affluent life thanks to her husband's high-paying job. But a year after his death, the 36-year-old is a grieving single mother deeply in debt and living paycheck to paycheck with her three children. Then an unexpected call from a well-known estate lawyer in New York offers a glimmer of hope. It is the beginning of a complex legal journey that could mean the difference between a life of abject poverty and unthinkable wealth thanks to her father, deceased billionaire Wallace Barclay. Thirty years before, Arden's mother Virginia Bunt, a flirtatious love addict with a string of failed affairs, met Wallace, an encounter that transformed her life. When he died unexpectedly without a will, Virginia fought to secure a comfortable future for her and the secret unborn daughter she shared with Wallace. Yet despite her best efforts, society and the legal system prevented her from receiving the money that should rightfully have been hers. Now, though, with changes in the legal system and science, her daughter Arden may finally succeed in claiming the inheritance that has been long denied. Told from both Arden and Virginia's viewpoints, straddling past and present, and moving from Toronto to New York City, The Inheritance is a poignant portrait of familial bonds, haunting pasts, the collateral damage of life choices, and the promise of hopeful futures as two venerable women fight for the life they deserve"--